Maternal adverse childhood experiences and perinatal outcomes: A retrospective inceptive cohort study - Amanda Troëng; Jessica Dolk; Marie-Therese Vinnars; Johan Hallqvist; Per Kristiansson (PLoS ONE, 2025)
Introduction Adverse childhood experiences (ACEs) are associated with poor health and social outcomes in adulthood. However, research on the relationship between ACEs and perinatal outcomes remains limited, and the effect of cumulative ACEs on perinatal outcomes has not yet been established. This study examines the association between maternal exposure to multiple ACEs and perinatal outcomes. Material and methods The study comprised a cohort study of 1,253 women enrolled in the national prenatal healthcare program in Sweden 2012-2013. In early pregnancy and one year after childbirth the women completed a total of 3 questionnaires that included questions on ACEs, mode of delivery, and birth complications. ACEs were grouped as involving 0, 1-3, or ≥4 categories according to previously defined measures. Multiple ordinal logistic regression analyses were used to compare perinatal outcomes across ACE categories adjusted for a minimal sufficient set of confounders as well as sensitivity analyses. Results The women had an average age of 32, and the majority were multiparous, of Swedish origin, highly educated, non-smokers and in a relationship. The proportions of women with adverse childhood experiences in the 0, 1-3, and ≥4 categories were 42%, 46% and 12%, respectively. On the whole, the adjusted odds ratios (aOR) were highest for women exposed to adverse childhood experience in ≥4 categories, with women exposed to 0 as reference, and with aORs for women exposed to 1-3 categories in between. In women with ≥4 ACEs categories, the strongest associations were found for the outcomes emergency Caesarean delivery (aOR 2.02, CI 1.13-3.63), bleeding >1000 ml in connection with Caesarean delivery (aOR 3.54, CI 1.01-12.39), preeclampsia (aOR 4.21, CI 1.73-10.25) and requiring antibiotics (aOR 3.14, CI 1.19-8.32). Conclusions Multiple ACEs were associated with higher rates of adverse perinatal outcomes. The maternal health services need to identify these individuals and provide extra care to mitigate their risks.